Traffic Safety Education for Students in Makassar City - Radjawane, Louise Elizabeth; Gracesy Prisela Christy; Singgih, Hanna M.; Margaritha Rami Ndoen (Salus Publica: Journal of Community Service, 2024)
The presence of motor vehicles aids in the improvement of goods and services distribution. However, motor vehicles are sometimes used inappropriately, including by students. The aim of the community service activity is to enhance students' awareness and understanding of traffic regulations. The activity was conducted at a junior/senior high school in Makassar City and involved 100 students. The methods used included administering a pre-test, providing materials, and conducting an evaluation (post-test) regarding traffic regulations for students. Traffic education for students was carried out effectively, increasing awareness and helping to reduce the number of accidents on the road